Which industrial policy does Europe need? - Mariana Mazzucato; Mario Cimoli; Giovanni Dosi; Joseph E. Stiglitz; Michael A. Landesmann; Mario Pianta; Rainer Walz; Tim Page (Intereconomics, 2015)
One lesson of the Great Recession has been that countries with higher shares of industry in their GDP seemed to be less affected by the crisis. Consequently, the call for an industrial renaissance has become stronger. Industrial policy has now become a top priority in countries where it was not explicitly considered in the past. A strong EU-wide industrial policy is expected to foster growth and job creation. However, cultivating industrial development is a complex challenge. This Forum addresses the steps that need to be taken to create a new European industrial policy. What are the structural challenges that need to be addressed? What are the instruments of the EU's industrial policy? And should the EU be engaged in picking winners, or is the market better at making such judgements?
Keywords: 330; Innovation; Industriepolitik; Technologiepolitik; Europa